RESPON PEMBERIAN PUPUK KANDANG LEMBU DAN ZPT ATONIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI (Capsicum frutescens L) VARIETAS CABAI RAWIT HIBRIDA DALAM POLYBAG - Yudi Triyanto (JURNAL AGROPLASMA, 2015)
The research was conducted in Dusun VI of Pangkatan Sub-district of Labuhanbatu Regency.The design of Randomized Block Design (RAK) Factorial with 2 factors studied was the factor of Kandang Lembu fertilizer (L) and ZPT Atonik (A) 12 combination of treatment: for the factor of Kandang Lembu fertilizer is L0 = 0 gr / polybag, L1 = 320 gr / polybag, L2 = 640 gr / polybag while the Axik ZPT is A0 = 0 cc / liter water, A1 = 1 cc / Liter of water, A2 = 2 cc / liter of water and A3 = 3 cc / liter of water. Parameters observed, height of plant (cm), stem diameter (cm), flowering plant age (day) and weight of sample plant fruit (gr). From the result of this research, it can be concluded: (1) The treatment of Kandang Lembu fertilizer gives a significant effect on the parameters of plant height, the weight of the sample plant and the stem diameter but does not give significant effect on the age of flowering plants; (2) The treatment of ZPT Atonik is not Showed significant effect on plant height parameters, stem diameter, flowering plant age and plant sample weight; (3) The interaction between cow manure and Atonik ZPT did not show any significant effect on all parameters: plant height, stem diameter, plant weight and weight of fruit of sample plant. Keywords: Manure Cow Manure, Atonik ZPT, Chili (Capsicum frutescens L), Hybrid Varieties